Effect of Hofmeister Ions on Transport Properties of Aqueous Solutions of Sodium Hyaluronate - Musilová, Lenka; Mráček, Aleš; Kašpárková, Věra; Minařík, Antonín; Valente, Artur J M; Azevedo, Eduarda F G; Veríssimo, Luis M P; Rodrigo, M Melia; Esteso, Miguel A; Ribeiro, Ana C F (International journal of molecular sciences, 2021)
Tracer diffusion coefficients obtained from the Taylor dispersion technique at 25.0 °C were measured to study the influence of sodium, ammonium and magnesium salts at 0.01 and 0.1 mol dm-3 on the transport behavior of sodium hyaluronate (NaHy, 0.1%). The selection of these salts was based on their position in Hofmeister series, which describe the specific influence of different ions (cations and anions) on some physicochemical properties of a system that can be interpreted as a salting-in or salting-out effect. In our case, in general, an increase in the ionic strength (i.e., concentrations at 0.01 mol dm-3) led to a significant decrease in the limiting diffusion coefficient of the NaHy 0.1%, indicating, in those circumstances, the presence of salting-in effects. However, the opposite effect (salting-out) was verified with the increase in concentration of some salts, mainly for NH4SCN at 0.1 mol dm-3. In this particular salt, the cation is weakly hydrated and, consequently, its presence does not favor interactions between NaHy and water molecules, promoting, in those circumstances, less resistance to the movement of NaHy and thus to the increase of its diffusion (19%). These data, complemented by viscosity measurements, permit us to have a better understanding about the effect of these salts on the transport behaviour of NaHy.
Keywords: osmolární koncentrace; biologický transport; soli; viskozita; Cations; chlorid lithný; síran amonný; Sodium Chloride; Solutions; voda; thiokyanatany; Ammonium Sulfate; Biological Transport; Viscosity; viscosity; kationty; roztoky; Water; Osmolar Concentration; Lithium Chloride; Anions; kyselina hyaluronová; anionty; difuze; Temperature; síran hořečnatý; Hyaluronic Acid; Salts; sodium hyaluronate; Diffusion; chlorid sodný; Hofmeister series; transport properties; Magnesium Sulfate; Sulfates; sírany; Thiocyanates; teplota